Supernumerary Robotic Limbs: A Review and Future Outlook - Yang, Bo; Huang, Jian; Chen, Xinxing; Xiong, Caihua; Hasegawa, Yasuhisa (IEEE transactions on medical robotics and bionics, 2021)
Wearable robots have become a prevalent method in the field of human augmentation and medical rehabilitation. Typical wearable robots mainly include exoskeletons and prostheses. However, their functions are limited due to dedicated design. In recent years, Supernumerary Robotic Limbs (SRLs) have become a hot spot in the field of wearable robots. Different from exoskeletons and prostheses, SRLs compensate and strengthen human abilities by providing extra limbs. This advantage allows SRLs to assist users in a novel way, rather than substituting missing limbs or enhancing existing limbs. However, finding a trade-off between wearability, efficiency, and usability of those SRLs is still an issue. This paper presents the state of the art in SRLs and discusses some open questions about SRLs' design and control for further research. This review covers the following areas: (1) Basic concepts and classifications of SRLs; (2) The literature retrieval methodology; (3) Design functions of different types of SRLs, including their positive and negative aspects; (4) Different control strategies of SRLs, including positive and negative aspects, and some improvement methods in applying SRLs; (5) The impact on human body schema while using SRLs; (6) Open challenges and suggestions for future development. This review will help researchers understand the current state of SRLs and provide comprehensive knowledge foundations for them.